Quantitative analysis of total serum glycome in human and mouse. Issue 21 (12th October 2016) - Yoshida, Yasunobu; Furukawa, Jun‐ichi; Naito, Shoichi; Higashino, Kenichi; Numata, Yoshito; Shinohara, Yasuro
Abstract : Model mice are frequently used in drug discovery research. Knowledge of similarities and differences between the mouse and human glycomes is critical when model mice are used for the discovery of glycan‐related biomarkers and targets for therapeutic intervention. Since few comparative glycomic studies between human and mouse have been conducted, we performed a comprehensive comparison of the major classes of glycans in human and mouse sera using mass spectrometric and liquid chromatographic analyses. Up to 131 serum glycans, including N‐glycans, free oligosaccharides (fOSs), glycosaminoglycans, O‐glycans, and glycosphingolipid (GSL)‐glycans, were quantified. In both serum samples, N‐glycans were the most abundant in the total serum glycome, while fOSs were the least abundant. As expected, the diversity of sialic acid (i.e. Neu5Ac vs. Neu5Gc) was the major species difference between human and mouse in terms of N‐ and O‐glycosylation, while GSL‐glycomic profiles were completely different, even when the sialic acid diversity was taken into consideration. Furthermore, total serum glycomics of STAM mouse were unveiled as an initial step to identify novel biomarkers of liver diseases, with which we could identify several glycans with expression significantly increased or decreased expression.